KONTRIBUSI PENGUASAAN MATA DIKLAT PRODUKTIF DAN MINAT SISWA TERHADAP KEBERHASILAN PRAKTEK KERJA INDUSTRI PROGRAM TEKNIK AUDIO DAN VIDEO (TAV) KELAS XI DI SMK NEGERI 5 PADANG - Musthafa Ramadhan; Titi Sriwahyuni; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
This study aimed to determine the contribution of Currency Mastery Training Productive and Interests Students Against Success Industrial Work Practice Program Audio and Video Engineering (TAV) Class XI in SMK Negeri 5 Padang.  This study is correlational description. The technique of sample selection in this study using simple random sampling of 39 respondents in SMK Negeri 5 Padang. Technique of collecting data using questionnaires and documentation. The data were analyzed using statistical methods of multiple regression analysis. The results of data analysis showed: 1) mastery currency productive training and interests of students together contribute significantly to the success of industry work practices outcomes of 61.5%, 2) mastery currency productive training contribute significantly to the success of industry work practices class outcomes of 47.5% and 3) student interest contributes significantly to the success of industry work practices outcomes of 57%. Key Word : Mastery Training Productive Currency, Interest Student, Success Industrial Work Practices.